Effect of nano particle CaO addition (1-5WT%) on superconductivity properties of (Bi-Pb) 2223 superconductor with coprecipitation method / Siti Suziani Abdullah - Abdullah, Siti Suziani (Universiti Teknologi MARA, Shah Alam, 2009)
The effect of nano particle CaO addition on the critical temperature (Tc) of BSCCO system with nominal starting composition of Bii,6Pb o.4Sr2Ca2Cu30io-x (Bi-2223) was studied. The (Bii.6Pb o.4Sr2Ca2Cu30io)-x (Bi-2223) superconductor with addition of nano CaO (l-5wt %) particle have been prepared using the coprecipitation (COP) technique. The (Bii.6Pb o.4Sr2Ca2Cu30io).x samples have been investigated by dc electrical resistance, for measuring critical temperature (rc).The dominance of high- Tc was observed for all samples as evidenced in the single step transition of (R-T) curves. The results show that the addition of nano CaO particle does not affect much on the Tc zero of the added sample. Tc zero for non added sample was obtained around 97 K whereas for samples with l-5wt% addition showed Tc zero in the range of 86-73 K. Resistivity versus temperature measurement (R-T) showed that all samples exhibited metallic behaviour. This behaviour resulted in the shifting of Tc zero toward lower temperature. A linear decrease in Tc with increase in the level concentration of nano Cao addition was observed. However, the COP samples showed better superconducting properties probably due to higher homogeneity resulted from mixing of sub-micron particles during sintering. In conclusion, the finding of this study reveals using COP method has some potential in high temperature superconductor compared with solid state method.